Nexus of poverty, energy balance and health - C P Mishra (Wolters Kluwer Medknow Publications, 2012)
Since the inception of planning process in India, health planning was an integral component of socio-economic planning. Recommendations of several committees, policy documents and Millennium development goals were instrumental in development of impressive health infrastructure. Several anti-poverty and employment generation programmes were instituted to remove poverty. Spectacular achievements took place in terms of maternal and child health indicators and expectancy of life at birth. However, communicable diseases and undernutrition remain cause of serious concern and non-communicable diseases are imposing unprecedented challenge to planners and policy makers. Estimates of poverty based on different criteria point that it has remained a sustained problem in the country and emphasizes on revisiting anti-poverty programmes, economic policies and social reforms. Poverty affects purchasing power and thereby, food consumption. Energy intake data has inherent limitations. It must be assessed in terms of energy expenditure. Energy balance has been least explored area of research. The studies conducted in three different representative population group of Eastern Uttar Pradesh revealed that 69.63% rural adolescent girls (10-19 years), 79.9% rural reproductive age group females and 62.3% rural geriatric subjects were in negative energy balance. Negative energy balance was significantly less in adolescent girls belonging to high SES (51.37%), having main occupation of family as business (55.3%), and highest per capita income group (57.1%) with respect to their corresponding sub-categories. In case of rural reproductive age groups, this was maximum (93.0%) in SC/ST category and least (65.7%) in upper caste group. In case of geriatric group, higher adjusted Odd's Ratio for negative energy balance for subjects not cared by family members (AOR 23.43, CI 3.93-139.56), not kept money (AOR 5.27, CI 1.58-17.56), belonging to lower and upper middle SES by Udai Pareekh Classification (AOR 3.73, CI 1.22-11.41), with lowest per capita income (AOR 15.14, CI 2.44-94.14) and in age group >80 years (AOR 5.76, CI 1.03-32.39). Of those in negative energy balance, 70.21% rural adolescent girls and 7 out of 10 geriatric subjects (activity based) were victims of CED. Extent of undernutrition and CED in rural reproductive age group females were more in those caste groups where energy deficit was also of higher magnitude. Energy balance must be visualized giving due consideration to the importance of exercise on human health. The evidence thus generated needs to be translated to the masses based on principles of translational research.